Population Pressure and the Transition to Agriculture (Global Journal of Human-Social Science, 2016)
Is it food shortage or food abundance which explains the transition from foraging to farming The academic literature is divided We use the notion of population pressure defined as the ratio of population density over the stock of wild food resources to answer this question We demonstrate that the significant changes of the population pressure are only temporary and have asymmetric effects on hunter-gatherers behaviors Food shortages increase population pressure but do not trigger the shift to agriculture Indeed the common property regime as well as the common sharing of resources and knowledge hinder any incentive to innovate and to produce more effort On the contrary food abundance induces the advent of exclusive property rights the disappearance of sharing and therefore stimulates effort and innovation Since food abundance is a feature of complex hunter-gatherer societies the latter are more likely at the origin of the transition to agriculture
Keywords: hunter-gatherer; complex hunter-gatherer; Neolithic revolution; sharing; population pressure; openaccess resources